Cognitive functioning and depressive symptoms in Fabry disease: A follow‐up study. Issue 5 (25th June 2020) - Körver, Simon; Geurtsen, Gert J.; Hollak, Carla E. M.; van Schaik, Ivo N.; Longo, Maria G. F.; Lima, Marjana R.; Dijkgraaf, Marcel G. W.; Langeveld, Mirjam
Abstract: Patients with Fabry disease (FD) have a high prevalence of depressive symptoms and can suffer from cognitive impairment, negatively affecting their life. The course of cognitive functioning and depressive symptoms in FD is unknown. The aim of this prospective cohort study was to describe changes in cognitive functioning and depressive symptoms and to identify related variables in patients with FD over 1 year. Assessments were conducted twice, using a neuropsychological test battery and the Centre of Epidemiological Studies Depression scale (CESD). Eighty‐one patients were included of which 76 patients (94%) completed both assessments (age: 44 years, 34% men, 75% classical phenotype). A significant decrease in cognitive functioning was found in four patients (5%), with patients regressing from excellent to average/good. Changes were not related to sex, phenotype, stroke, IQ or CESD scores. CESD scores ≥16 were present in 29 patients (38%) at baseline. Using the reliable change index a decrease in CESD scores was found in six patients (8%). Decreased CESD scores were independently related to employing a positive and problem solving coping style and increased CESD scores to an avoiding and brooding coping style and worsening health perception. We found no major changes in cognitive functioning in patients with FD during 1 year follow‐up making it an unsuitable outcome in FD treatment trials. Considering the high prevalence of persistent depressive symptoms, assessment of depressive symptoms should be part of routine follow‐up. Altering coping styles and health perception may improve psychological well‐being in FD. Abstract :